Incidence and Early Course of Retinopathy of Prematurity: Secondary Analysis of the Postnatal Growth and Retinopathy of Prematurity (G-ROP) Study - Quinn, Graham E. (JAMA Ophthalmol, 2018)
IMPORTANCE: The current guidelines for retinopathy of prematurity (ROP) detection programs in the United States include a range of birth weights (BWs) and gestational ages and likely require examinations of many premature infants who are at low risk for developing serious retinopathy. OBJECTIVE: To determine the incidence, onset, and early course of ROP in what to our knowledge is the largest cohort to date that is representative of infants who are undergoing ROP screening. DESIGN, SETTING, AND PARTICIPANTS: This secondary analysis of data from the Postnatal Growth and Retinopathy of Prematurity (G-ROP) retrospective cohort study was conducted in 29 hospitals in the United States and Canada between January 2006 and December 2011 and included 7483 infants who underwent serial ROP examinations. MAIN OUTCOMES AND MEASURES: Most severe ROP in either eye, classified as no ROP, mild ROP, type 2 ROP, or type 1 ROP (per Early Treatment for ROP Study criteria). Onset at postmenstrual age for zone I disease and stage of ROP, plus disease, and treatment. RESULTS: This study included 7483 infants with a mean (SD) BW of 1099 (259) g and a mean (SD) gestational age of 28 (3) weeks who underwent ROP examinations. Of these, 3224 infants (43.1%) developed ROP, 459 (6.1%) developed type 1 and 472 (6.3%) type 2 ROP, 514 (6.9%) underwent treatment in 1 or both eyes, and 147 (2%) had zone I disease. Additionally, 98.1% of type 1 or 2 ROP cases occurred in infants with a BW of less than 1251 g. Only about half of the eyes (49.4%) were vascularized into zone III by 37 weeks postmenstrual age. CONCLUSIONS AND RELEVANCE: These findings add to our knowledge of ROP screening as they include all eligible infants, not just high-risk infants as in previous studies. More than 40% of at-risk premature infants develop some stage of ROP, and most retinopathy regresses without treatment. However, approximately 12.5% develop severe ROP, which occurs almost exclusively among infants with a BW of less than 1251 g.